Praktik Doa dan Puasa yang Berkenan Menurut Kitab Ester : Refleksi Teologis dan Implikasinya bagi Pembentukan Kerohanian Orang Percaya Masa Kini - Jeremia Teguh Setiawan; Yanto Paulus Hermanto (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study is motivated by the importance of prayer and fasting practices in the Christian tradition, which are increasingly marginalized in the midst of modern secularism and individualism. The purpose of this study is to analyze the concept of prayer and fasting based on the principles in the Book of Esther and to examine its implications for the formation of contemporary Christian spirituality. This research employs a literature review method by examining biblical texts and contemporary theological literature to identify the characteristics of prayer and fasting that are pleasing to God. The results of the study indicate that the practice of prayer and fasting in the Book of Esther is not merely ritualistic, but an expression of faith, self-denial, and communal solidarity that leads to personal transformation and strengthened social sensitivity. The implication of this study is that the principles of prayer and fasting in the Book of Esther can serve as a model for the spiritual formation of the modern church, fostering intimacy with God and a commitment to addressing surrounding social issues. These findings contribute to the development of practical theology and contemporary Christian spirituality studies.